С. Петлюра як політичний лідер УНР в умовах еміграції: міжнародний і український контексти - Піскун, В.М. (Інститут історії України НАН України, 2009)
У статті висвітлюється діяльність Симона Петлюри як політичного лідера УНР в еміграції на тлі міжнародних подій та у контексті сприйняття його особистості в Україні. Головна увага зосереджена на таких вимірах постаті Петлюри: державний діяч, носій традицій незалежної УНР; політичний діяч, адепт європейського вектора розвитку України й добросусідських відно син із Польщею; лідер, якого підтримували вихідці з різних регіонів України, поділяючи його наддніпрянський централізм. The article highlights the activity of Symon Petliura as UNR politician. Since November 1920 till his death in May 1926 he had been in emigration in Poland and France. The personality of Symon Petliura is viewed against the background of international events and in context of his acceptance in Ukraine. The author focused on 3 aspects: Petliura as a statesman and supporter of independent UNR’s traditions who considered Bolsheviks as occupants of Ukraine and fought for its liberation; as a politician who advocated European development of Ukraine and goodneighborly relations with Poland; and as a leader supported by Ukrainian immigrants who shared his Upper-Dnipro central political views.